Boosting English Vocabulary Acquisition through Daily Duolingo Practice: A Pre-Experimental Study on Pharmacy Students (Lembaga Pengembangan Kinerja Dosen, 2026)
Education involves acquiring knowledge and skills, with English learning being a skill-based process that requires consistent and engaging practice. In the digital era, mobile applications have emerged as effective tools to overcome traditional limitations in language learning. This study investigates the effectiveness of the Duolingo application in enhancing English vocabulary among university students. A pre-experimental one-group pretest-posttest design was employed involving 40 first-semester Pharmacy students at Anwar Medika University. Participants engaged in daily Duolingo practice (20 XP per day) for 30 consecutive days. Data were collected through vocabulary pretest and posttest as well as a Likert-scale questionnaire. Quantitative analysis revealed a significant improvement in vocabulary scores, with the mean score increasing from 57.25 in the pretest to 81.70 in the posttest. Questionnaire results indicated high student motivation, positive perceptions of the app’s usefulness and ease of use, and minimal perceived disadvantages. The findings suggest that daily Duolingo practice is an effective, engaging, and accessible method for boosting English vocabulary acquisition. This study provides practical insights for educators seeking innovative technology-integrated approaches to language teaching.